Penggunaan Media Lidimatika Untuk Meningkatkan Keterampilan Berhitung Perkalian Siswa Kelas 3 UPT SDN 98 Gresik - Pratiwi Lia Ayu Susanti; Arissona Dia Indah Sari; Arya Setya Nugraha (STIKes Ibnu Sina Ajibarang, 2024)
The background to this PTK problem is that students have not been able to master the concept of multiplication material. So there is a need for learning media as a student learning resource that is able to help students' understanding process regarding multiplication of numbers in mathematics with the help of linguistic learning media. This classroom action research aims to improve multiplication counting skills in class 3 of UPT SDN 98 Gresik. The research used was Classroom Action Research (PTK) which was designed in 2 cycles with 4 stages. The four stages of the research action cycle are as follows: 1) planning, 2) implementing, 3) observing, and 4) reflecting. Based on the research results obtained, it is known that the average initial data completeness score for 20 students was 52.75%, before the application of the linguistics learning media. The average score for cycle I was 66, or 8 students with a percentage of 40% who had completed or above the KKM and 12 students with a percentage of 60% who had not completed or below the KKM because they had exceeded the predetermined criteria of 75 and continued in cycle II. In conclusion, linguistic learning media can improve multiplication calculation skills.